Nursing Care for Patients with Atrial Fibrillation in the Intensive Care Unit: Case study - Charista, Helvin Eka (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2024)
Atrial fibrillation is a typical supraventricular tachyarrhythmia, with undirected atrial activation resulting in a decrease in atrial mechanical function. Objective: To identify an overview of the case study of nursing care for patients with atrial fibrillation (AF) in the Seruni ICU at Mardi Waluyo Hospital. Method: This research uses a case study design specifically designed to study in detail and in depth about a case and includes various sources of information. Results: The main nursing diagnoses that emerged in 2 managed patients were decreased cardiac output and activity intolerance. The interventions prescribed for patients with atrial fibrillation are in accordance with previously existing diagnoses and theories. The implementation carried out in patients with atrial fibrillation is in accordance with previously established interventions and adapted to the patient's condition and situation. Conclusion: The condition improved in case 1, and the problem was resolved, but in case 2 the problem was not resolved; the patient died.